Self-supporting metal-based nanofilm electrocatalyst for sustainable hydrogen production

By using large-area self-supported metal-based nanofilm electrocatalysts in electrochemical water electrolysis technology, highly distorted metal nanocrystals are formed through nano-scale amorphous carbon interface bonding, the scarcity and high cost of platinum catalysts are solved, and the problem of platinum catalysts is achieved. It has efficient and low-cost hydrogen evolution reactions, and has excellent stability and ease of manufacturing.

CN119194495APending Publication Date: 2024-12-27CITY UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410825551.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-13
Filing Date
2024-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The lack of cost-effective and stable catalysts in existing electrochemical water electrolysis technologies, especially the scarcity and high cost of platinum (Pt) catalysts limit their wide application, and traditional synthesis methods require high temperature environments and expensive equipment, resulting in high energy consumption and High cost.

Method used

A large-area self-supported metal-based nanofilm electrocatalyst was developed to form highly distorted metal nanocrystals through nanoscale amorphous carbon interface bonding, and prepared by polymer surface buckling and peeling method to achieve efficient synthesis of platinum nanofilms. There is an overpotential of less than 30 mV and a Tafir slope of 30 mV/dec to 37 mV/dec.

Benefits of technology

Excellent hydrogen evolution reaction performance is achieved, production costs are reduced, catalyst stability and manufacturing ease, and is free of binder, and is cost-effective than traditional Pt foil catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194495A_ABST
    Figure CN119194495A_ABST
Patent Text Reader

Abstract

The present invention provides an easy-to-implement method for manufacturing ultra-thin Pt nanomembranes that are significantly lower in cost of catalyzing HER than commercial Pt / C and comparable to non-noble metal electrocatalysts. These Pt nanofilms consist of highly distorted Pt nanocrystals and exhibit a heterogeneous elastic strain field, which is rarely seen in conventional crystals. This unique feature results in significantly higher electrocatalytic efficiency compared to various forms of Pt electrocatalysts, including Pt / C, Pt foil, and many Pt monatomic or single cluster catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 510,363 filed on June 26, 2023 and U.S. Patent Application No. 18 / 741,839 filed on June 13, 2024, and the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0002] The present invention relates generally to the field of material science. More specifically, the present invention relates to highly distorted platinum (Pt) nanofilm catalysts that are ultra-efficient but low-cost. Background Art

[0003] In recent years, people have been pursuing a sustainable economy, and electrochemical water electrolysis / decomposition technology has attracted widespread attention as an attractive method. This method includes advantages such as fast kinetics and high hydrogen purity. By decomposing water molecules into hydrogen and oxygen, electrochemical water electrolysis provides an environmentally friendly and renewable method for hydrogen energy production, reducing dependence on traditional energy and being environmentally friendly.

[0004] However, despite the great potential of electrochemical water electrolysis, the lack of economical, efficient and stable catalysts has been a key factor restricting its development. Catalysts play a vital role in electrochemical water electrolysis. Catalysts can reduce energy requirements, increase reaction rates and improve the selectivity of chemical reactions, thereby achieving a more efficient water electrolysis process. Platinum (Pt) is known as one of the best catalysts for hydrogen evolution reaction (HER) due to its suitable binding energy. Platinum exhibits excellent characteristics, including low overpotential and high current density. However, the scarcity and high cost of Pt limit its widespread application.

[0005] To date, various synthetic strategies have been developed to maximize the catalytic potential of Pt, such as wet chemical methods and atomic layer deposition (ALD). For example, Tiwari et al. 1 Following a multi-step process involving grinding, heating at 750 °C, acid leaching, and electrochemical deposition, a multicomponent catalyst with ultralow Pt loading was synthesized on melamine-derived graphite tubes. Liu et al. 2 Atomically dispersed Pt was formed by oxidizing detonation nanodiamond (DND) powder at 160°C for 24 hours, followed by thermal deoxidation, oxidation with HNO3 for 4 hours, and finally depositing Pt on curved carbon by ALD. Although the prior art has achieved promising results, these methods usually require high temperature environments and / or expensive equipment, resulting in high energy consumption and high costs. In addition, the production yield is relatively low, which highlights the importance of developing a catalyst with high yield and high cost-effectiveness. Summary of the invention

[0006] Existing catalysts are usually high in cost, poor in stability, and insufficient in activity, which limits the practical application and commercialization of electrochemical water electrolysis technology. Therefore, the object of the present invention is to provide a series of metal-based nanofilm electrocatalysts that exhibit highly distorted metal nanocrystals bonded together by nanoscale amorphous carbon interfaces.

[0007] Specifically, in a first aspect, the present invention provides a large-area self-supporting metal-based nanofilm electrocatalyst for sustainable hydrogen production, which comprises one or more metal nanocrystals with lattice expansion. The one or more metal nanocrystals include highly distorted heterogeneous nanostructures, and they are bonded together by nanoscale amorphous carbon interfaces. Lattice distortion and heterogeneous strain are induced in the large-area self-supporting metal-based nanofilm electrocatalyst to enhance hydrogen evolution reaction performance.

[0008] In one embodiment, the large-area self-supporting metal-based nanofilm exhibits a heterogeneous distribution of local conductivity characterized by highly conductive nanodomains surrounded by less conductive regions.

[0009] In one embodiment, the highly distorted heterogeneous nanostructure comprises FCC nanocrystals and amorphous regions between clusters of FCC nanocrystals.

[0010] In one embodiment, the metal is selected from gold, platinum, silver, titanium, palladium, ruthenium, iridium or other high entropy alloys, or combinations thereof.

[0011] In another embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst comprises 20-80 at % of platinum, 10-50 at % of carbon, and 1-30 at % of oxygen.

[0012] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst has a thickness in the range of 1 nm to 30 nm, and the average size of the one or more metal nanocrystals is between 1 nm and 10 nm.

[0013] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst is binder-free.

[0014] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst is synthesized by polymer surface buckling peeling, which includes: using a polymer layer on a substrate as a scaffold for supporting a metal film; inducing controlled buckling on a polymer surface; and peeling off the metal film to obtain the large-area self-supporting metal-based nanofilm electrocatalyst.

[0015] In one embodiment, the substrate comprises a glass plate or a silicon wafer. The polymer comprises polyvinyl alcohol.

[0016] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst exhibits an η10 value of less than 30 mV.

[0017] Preferably, the large-area self-supporting metal-based nanofilm electrocatalyst exhibits an η10 value of 26mV to 29mV.

[0018] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst exhibits a Tafel slope in the range of 30 mV / dec to 37 mV / dec.

[0019] On the other hand, the large-area self-supporting metal-based nanofilm electrocatalyst has many potential applications, especially as a catalyst. For example, the catalyst can be used in a water splitting device. In addition to the water splitting device, the present invention can also be applied to the synthesis of electrocatalysts in fuel cells.

[0020] The Pt nanofilm of the present invention has the following advantages: (1) excellent HER performance; (2) a promising approach to developing high-efficiency and low-cost low-dimensional electrocatalysts; (3) easy fabrication; (4) good stability; and (5) no binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:

[0022] Figure 1 A schematic diagram of a proton exchange membrane fuel cell according to an embodiment of the present invention is shown;

[0023] Figure 2 Pt loading content of nanofilms of different thicknesses measured by inductively coupled plasma optical emission spectroscopy (ICP-OES) is depicted;

[0024] Figure 3A A photograph showing a 19 nm thick free-standing Pt nanofilm on a water surface; Figure 3B A height profile image of a transferred Pt nanofilm (5 nm, 10 nm, 19 nm, and 28 nm in thickness) on silicon is shown; the inset shows an AFM image across the edge of the Pt nanofilm; Figure 3C The X-ray diffraction pattern of 19 nm Pt nanofilm is depicted; Figure 3D Conductive atomic force microscopy (C-AFM) images of 19 nm thick nanofilms are shown, and a magnified view is shown on the right; Figure 3E A low-magnification TEM image of a 19-nm-thick free-standing Pt nanofilm is shown, and the inset shows the corresponding SADP; Figure 3FDepicted is the radially integrated intensity of the diffraction pattern of the free-standing nanofilm compared to the diffraction pattern of single-phase FCC bulk Pt as indicated by the dashed line; Figure 3G shows a HAADF-STEM image from the

[011] direction of a typical platinum nanoparticle with an FCC structure; Figure 3H A high-resolution TEM image of a 19 nm thick Pt nanofilm is shown; the inset is a fast Fourier transform (FFT) image of the amorphous region (upper right) and the crystalline region (lower left); Fig. 3I High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images of typical PtNCs with FCC structure and the corresponding elemental maps of Pt, C, and O are shown; Figure 3J The variation of lattice constant of Pt nanocrystal (NC) with the size of nanocrystal is depicted;

[0025] Figure 4A Shows Figure 3H Inverse fast Fourier transform (IFFT) analysis of high-resolution TEM images of typical Pt NCs with FCC structure; Figure 4B Shows Figure 4A The normal strain ε xx Contour map of ; Figure 4C shows the strain ε xx Distribution of components;

[0026] Figure 5A A low magnification TEM image of a 5 nm Pt nanofilm is shown; Figure 5B shows the magnified TEM images of Pt nanoparticles and amorphous carbon, and the corresponding FFT images; Figure 5C HAADF-STEM images and corresponding elemental maps of Pt, C, and O are shown; Figure 5D A high-resolution TEM image is shown, revealing the vacancy defects in the

[001] direction. Figure 5E Depicted is a line scan of the intensity, showing the location of the Pt vacancies;

[0027] Fig. 6A Depicted is the X-ray photoelectron spectroscopy (XPS) depth profiling of Pt nanofilms; narrow scan XPS spectra of Pt 4f, C ls, and Ols as a function of etching time; Figure 6B The relative atomic concentrations of Pt, C, and O obtained from the quantitative analysis of XPS with etching time are depicted; Figure 6C The X-ray absorption near-edge structure (XANES) at the Pt L3 edge is depicted; Fig.6D FT-EXAFS region depicting the local structure of Pt; Fig. 6E The FT-EXAFS spectra of the first shell of Pt foil and 19 nm Pt nanofilm in r-space and the corresponding least squares fits are depicted; Fig. 6F The EXAFS χ(k) signals of Pt foil and 19 nm Pt nanofilm in k-space and the corresponding least squares fits are depicted; Figure 6G The EXAFSχ(k) signal in k-space is depicted; Figure 6H Wavelet transforms of the k3-weighted EXAFS Pt K-edge signals of Pt foil and Pt nanofilm are shown, respectively;

[0028] Fig. 7A SEM images of pure carbon cloth, 5 nm, 10 nm, 19 nm, and 28 nm thick nanofilms transferred onto carbon cloth are shown; Figure 7B A linear scan of a carbon cloth transferring a 19 nm thick nanofilm is shown; Figure 7C Energy dispersive X-ray spectroscopy (EDS) of carbon cloth with 19 nm thick nanofilm is shown; Fig.7D The LSV curves of 5 nm, 10 nm, 19 nm, and 28 nm thick nanofilms and bulk Pt sheets are depicted; Fig. 7E The Tafel slopes of 5 nm, 10 nm, 19 nm, and 28 nm nanofilms and bulk Pt sheets are depicted;

[0029] Fig. 8A Electrochemical impedance spectroscopy (EIS) of 5 nm, 10 nm, 19 nm, and 28 nm thick nanofilms and bulk Pt sheets are depicted; Figure 8B The cyclic voltammetry (CV) curves of 5 nm, 10 nm, 19 nm, and 28 nm thick nanofilms and Pt foil at a scan rate of 50 mV / s are depicted;

[0030] Fig. 9 The mass activity comparison of Pt sheet, Pt nanofilm and commercial Pt / C at 50 mV potential is depicted;

[0031] Fig. 10A Pt nanofilms with different thicknesses (5 nm, 10 nm, 19 nm, and 28 nm) at 10 mA cm -2 Stability test under current density of ; Fig. 10B Depicted 10mA / cm 2 The overpotential and Tafel slope of the HER electrocatalysts are compared with those of other reported HER electrocatalysts.

[0032] Fig.11 shows 10 mA / cm at 24 hours 2 SEM image of 19 nm Pt nanofilm transferred onto carbon cloth after stabilization;

[0033] Fig.12Shown is the performance of a proton exchange membrane water electrolyzer (PEM-WE) device using a 19 nm Pt nanomembrane as a cathode HER catalyst and commercial IrO2 as an anode OER catalyst at room temperature. The inset is a schematic diagram (left) and a photograph (right) of the PEM-WE.

[0034] Fig.13A shows the comparison between the experimental force-displacement curve of a 19 nm thick Pt nanofilm under AFM indentation and FEA simulation; Fig. 13B shows the AFM scanning images of the suspended Pt nanofilm before and after indentation; Fig. 13C Comparison of yield strength and ductility of Pt nanofilms with nanocrystalline (NC) and polycrystalline (PC) Pt films, bulk Pt, and Pt nanowires (NWs) is shown; Fig.13D A comparison of the Young's modulus of Pt nanofilms, Pt nanoparticles (NPs), and bulk Pt is shown;

[0035] Fig.14A The atomic configuration of a Pt nanocrystal containing substituted C atoms is shown, along with the distribution of local shear strain reflected by color coding; Fig. 14B The distribution of shear strain and volume strain obtained by Pt nanocrystals with / without surface atoms are shown respectively;

[0036] Fig.15 The projected density of states (DOS) of the original Pt and distorted Pt surfaces when the crystals are oriented (111), (110), and (100), respectively, are shown, and the dotted line indicates the Fermi level;

[0037] Fig.16A The adsorption free energy of the conventional crystal with uniform tensile strain ranging from 0% to 7% relative to the reaction coordinate of HER and the adsorption free energy of the distorted crystal with heterogeneous tensile strain ranging from 0% to 7% relative to the reaction coordinate of HER are shown; Fig. 16B The free energy of the conventional crystal and the distorted crystal with orientations of (111), (110) and (100) is compared with the strain. The inset is the strain of the distorted crystal and the conventional crystal in the (111) orientation. Fig. 16C The adsorption free energy of a distorted crystal with 2 vacancies with heterogeneous tensile strain ranging from 0 to 7% and the adsorption free energy of a distorted crystal with 3 vacancies with heterogeneous tensile strain ranging from 0-7% are shown with respect to the reaction coordinate of HER. Fig.16D Simulations of substitutional defects C or O and adsorption free energy of non-distorted Pt nanocrystals are shown.

[0038] Fig.17 Shown at 10mA / cm 2 Comparison of overpotential and unit area cost with pure Pt foil. DETAILED DESCRIPTION

[0039] The widespread adoption of highly efficient electrocatalysts such as platinum (Pt) is hampered by their high cost. Conventional Pt catalysts are usually used in powder form, which poses challenges due to their limited surface area, limited resource availability, and high cost. Therefore, the development of an efficient and cost-effective Pt catalyst and its preparation process is of great significance.

[0040] Therefore, the present invention provides a large-area self-supporting metal-based nanofilm electrocatalyst for sustainable hydrogen production, which comprises one or more metal nanocrystals with lattice expansion. The one or more metal nanocrystals include highly distorted heterogeneous nanostructures, and they are bonded together by nanoscale amorphous carbon interfaces. Lattice distortion and heterogeneous strain are induced in the large-area self-supporting metal-based nanofilm electrocatalyst to achieve enhanced hydrogen evolution reaction performance.

[0041] It is noteworthy that the large-area self-supporting metal-based nanofilms exhibit a heterogeneous distribution of local conductivity, which is characterized by high-conductivity nanodomains surrounded by regions with lower conductivity. The highly distorted heterogeneous nanostructures can be FCC nanocrystals and amorphous regions located between FCC nanocrystal clusters.

[0042] In one embodiment, the metal may include gold, platinum, silver, titanium, palladium, ruthenium, iridium or other high entropy alloys, or combinations thereof.

[0043] Preferably, the metal is platinum (Pt). The prepared Pt nanofilms exhibit excellent HER, outperforming the benchmark catalyst commercial Pt foil. More importantly, the cost of Pt nanofilms is very low compared to non-precious metals, due to the ultra-thin depth within the amorphous carbon and the aggregation of individual Pt nanoparticles.

[0044] Preferably, the large-area self-supporting metal-based nanofilm electrocatalyst may contain 20-80 at % of platinum, 10-50 at % of carbon and 1-30 at % of oxygen.

[0045] By using the polymer surface buckling peeling (PSBEE) method 3-5 Large-area free-standing 2DPt nanofilms were prepared. The nanofilms exhibited excellent HER performance with small overpotential, good stability, and high turnover frequency (TOF), outperforming the benchmark catalyst commercial Pt foil.

[0046] The polymer surface buckling peeling comprises the following steps: (1) Using a polymer layer on a substrate as a scaffold for supporting a metal film; (2) inducing controlled buckling on a polymer surface; and (3) Peeling off the metal film to obtain the large-area self-supporting metal-based nanofilm electrocatalyst.

[0047] The PSBEE method provides a low-cost, high-yield, and easy-to-implement method. The simplicity of the method, coupled with the ultra-thin thickness of the nanofilm, reduces both production and material costs, making the 2D Pt catalyst of the present invention even more cost-effective than Pt foil ( Figure 1 ). These 2D Pt nanofilms provide a new mechanism for efficient catalyst design strategy: lattice distortion-induced heterogeneous strain.

[0048] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst is binder-free.

[0049] In one embodiment, the thickness of the large-area self-supporting metal-based nanofilm electrocatalyst is in the range of 1 nm to 30 nm. The average size of the one or more metal nanocrystals is between 1 nm and 10 nm.

[0050] In one embodiment, the depth of the metal nanofilm is in the range of 1 nm to 100 nm.

[0051] Preferably, the depth of the metal nanofilm is in the range of 5 nanometers to 76 nanometers.

[0052] In another embodiment, the metal nanofilm has metal nanocrystals having a size of 1 nm to 10 nm.

[0053] Preferably, the metal nanofilm has platinum nanocrystals having a size of 3 nanometers to 7 nanometers.

[0054] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst exhibits an η10 value of less than 30 mV, less than 25 mV, or less than 20 mV.

[0055] In one embodiment, the large-area self-supporting metal-based nanofilm electrocatalyst exhibits a Tafel slope in the range of 30 mV / dec to 37 mV / dec.

[0056] Examples

[0057] Example 1 - Materials and Methods

[0058] Electronic Characterization

[0059] Atomic force microscopy (AFM, MFP-3D Origin, Oxford Instruments), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) were used to characterize and measure the structural and chemical properties of the metal nanofilms.

[0060] For example, the self-supporting Pt nanofilm was transferred to various substrates such as Si wafers and TEM grids. Then, the thickness and surface morphology of the prepared Pt nanofilm on the Si wafer were checked using AFM, and the thickness and surface morphology of the Pt nanofilm on the grid were checked using a conventional field emission TEM (JEM-2100, JEOL) with an accelerating voltage of 200 kV and a Cs-corrected thermal field emission TEM (ARM200F, JEM) with a 300 kV acceleration voltage. Agilent 720ES (OES) was used to determine the Pt loading content of different thicknesses and the Pt ion concentration after the stability test.

[0061] Data reduction, analysis, and EXAFS fitting were performed using the Athena and Artemis programs in the Demeter data analysis software package. These programs utilize the FEFF6 program to fit the EXAFS data. The sample was energy calibrated using a standard Pt foil as a reference while the reference was measured. A linear function was subtracted from the pre-edge region, and the edge jump was normalized using the Athena software. The χ(k) data were separated by subtracting a smooth third-order polynomial that approximated the absorption background of isolated atoms. The k3-weighted χ(k) data were Fourier transformed after applying the Hanning window function (Ak=1.0). For EXAFS modeling, the global amplitude EXAFS (CN, R, σ 2 The EXAFS of Pt foil was fitted and the obtained amplitude reduction factor S0 was set in the EXAFS analysis. 2 value (0.839) to determine the coordination number (CN) in the Pt-C / O / Pt scattering path in the sample.

[0062] Mechanical characterization

[0063] The mechanical properties of the prepared Pt nanofilm were characterized using AFM-based indentation. The self-supporting Pt nanofilm was transferred to a porous Si wafer and suspended above the hole. A diamond-coated silicon tip (NC-LC, Adama) with a tip radius of 30 nanometers was used to perform indentation measurements at a rate of 300nm / s. Pt nanofilms with a thickness of 19 nanometers and 28 nanometers were tested under ambient conditions, wherein each group consisted of 15 nanofilms. The Young's modulus, yield strength and ductility of the Pt nanofilm were obtained from these data sets. The data set was extracted from the finite element analysis (FEA) performed using commercial software ANSYS (ANSYS Inc., USA). In the theoretical model, the suspended nanofilm in the actual experiment was modeled as an axisymmetric film with a radius of 1 μm to 2 μm. A rigid frictionless sphere with a radius of 30 nanometers was used to replace the AFM tip in the model. Based on platinum, the Poisson's ratio of the nanofilm was taken as 0.35. Then, Young's modulus and yield strength were determined by fitting using elastic and elastoplastic constitutive equations. In addition, the ductility of the Pt nanofilm was determined based on the maximum von Mises strain generated just before strain softening.

[0064] Electrochemical measurements

[0065] In a typical test, a self-supporting 2D Pt nanofilm was transferred to a commercial carbon cloth. After peeling off from the PVA substrate, the Pt nanofilm floated on the water surface. Then, the carbon cloth was submerged under water and the Pt nanofilm was selectively "scooped out". Using this method, controlled loading of Pt nanofilms onto commercial carbon cloth was successfully achieved, followed by drying at room temperature. All measurements were performed at room temperature in a standard three-electrode system using a H2-saturated 0.5M H2SO4 electrolyte. A carbon rod (diameter = 6 mm) was used as the counter electrode and a saturated calomel electrode (SCE) was used as the reference electrode. Under H2-saturated electrolyte conditions, the saturated calomel electrode (SCE) was calibrated as a reversible hydrogen electrode (RHE), while Pt foil was used as both the working electrode and the counter electrode, as shown below: E RHE =E SCE ~~0.27V

[0066] Electrochemical impedance spectroscopy measurements were performed at an overpotential of 10 mV vs. RHE with an AC potential of 10 mV at 10 5 Hz to 0.01 Hz. In addition, by maintaining the current density at 10 mA / cm 2 The time-dependent potential curves were collected for 24 hours.

[0067] T OF and active site density calculations

[0068] The total number of hydrogen conversions was calculated from the current density using the following formula: The Pt loading L was determined by inductively coupled plasma optical emission spectroscopy (ICP-OES) measurement ( Figure 2 ). Therefore, the active site density on bulk Pt is:

[0069] In the present invention, the potential calculated by TOF is 100 mV, where the current density of the 5 nm, 10 nm, and 19 nm thick nanofilms is 74.7 mA / cm 2 、83.8mA / cm 2 and 89.7mA / cm 2 :

[0070] Theoretical calculations

[0071] First-principle total energy calculations were performed using the Vienna As-is Simulation Package (VASP) and the Projector Augmented Wave (PAW) method. A plane wave cutoff energy of 400 eV was used. The convergence criteria for energy and force were set to 10 -5 eV and A 4 × 4 supercell with eight atomic layers was constructed to simulate Models I and II of Pt(111), (110), and (100), which incorporates more than A vacuum layer is formed to prevent periodic interactions. A tensile strain ranging from 0% to 7% is applied along the x-axis, which correspondingly increases the elastic strain of the unit cell. In this unit plate cell, the vacancy concentration increases by 6.25% (up to 18.75%), where the vacancy concentration is defined as the total number of vacancies divided by the total number of atoms in the original basal plane.

[0072] The Gibbs free energy of H adsorption (AG H *), a widely used descriptor for correlating theoretical predictions of catalytic activity in various systems with experimental measurements, is calculated using the following formula: in represents the hydrogen adsorption energy, ΔE ZPE represents the zero-point energy correction term, T is the temperature (298.15 K), and ΔS represents the entropy difference.

[0073] The best catalytic activity is obtained by AG close to zero H * indicates that the adsorption is too strong or too weak, respectively.

[0074] MD simulations were performed using the Large Scale Atom / Molecular Massively Parallel Simulator (LAMMPS) software package. These simulations utilized empirical force fields described by the improved embedded atom method (MEAM) potential of the Pt-C system. In order to observe the lattice distortion effect, approximately 20% of C atoms were introduced as substantial defects in Pt nanocrystals with a nanocrystal size of approximately 10 nanometers. The atomic configuration was visualized using OVITO software.

[0075] Example 2

[0076] Synthesis of Pt nanofilm

[0077] By using the polymer surface buckling peeling (PSBEE) method ( Figure 3A ) to manufacture large-area self-supporting 2D Pt nanofilms with thicknesses ranging from 5 nm to 28 nm. In one embodiment, a polyvinyl alcohol (PVA) hydrogel layer on a glass plate is used as a scaffold for supporting the Pt film. The Pt film is deposited on top of the PVA layer using physical vapor deposition. The thin Pt film is peeled off by inducing controlled buckling on the polymer surface. The Pt-PVA glass system is then immersed in deionized (DI) water. After a few minutes, the self-supporting nanosheets spontaneously peel off from the PVA substrate, thereby forming a large-area self-supporting Pt nanofilm.

[0078] In another embodiment, the glass plate can be replaced by other suitable substrates, and the smooth surface can be spin-coated with polyvinyl alcohol hydrogel. For example, a silicon wafer is a suitable substrate.

[0079] Example 3

[0080] Characterization of Pt nanofilms

[0081] refer to Figure 3B , which shows transmission electron microscopy (TEM) images of Pt nanofilms. The thickness of these 2D Pt can be easily varied from 5 nm to 28 nm, while the in-plane size remains at about 1 cm. Figure 3C , XRD results show that the diffraction peaks are consistent with those of bulk FCC Pt and exhibit considerable peak width. The explanation for the peak broadening in metal XRD spectra includes a variety of factors, such as lattice strain, dislocations, and grain boundaries, so direct observation using TEM remains a reliable method for characterizing lattice distortion in metals.

[0082] refer to Figure 3D, the conductive AFM (C-AFM) scan can be inferred that the Pt nanofilm of the present invention exhibits a heterogeneous distribution of local conductivity, in which high-conductivity nanodomains are surrounded by nanodomains with lower conductivity. Such conductivity distribution reflects the heterogeneous nanostructure of the Pt nanofilm. As shown in the corresponding selected area diffraction pattern (SADP) (inset) ( Figure 3E ), the heterogeneous nanostructure is formed by the stacking of FCC atoms.

[0083] refer to Figure 3F , using 2D SADP and integrating it with respect to the diffraction angle, we successfully calculated a series of 1D diffraction peaks. These peaks align with the typical FCC diffraction pattern, except for a clear shift to lower wavenumbers. This shift indicates that there is an overall tensile strain in the FCC lattice within the Pt nanofilm. Figure 3G Scanning transmission electron microscopy (STEM) of a Pt nanofilm is shown, demonstrating the presence of FCC nanocrystals (NCs). Figure 3H High-resolution TEM (HRTEM) of the Pt nanofilm is shown, demonstrating the presence of amorphous regions between FCC nanocrystal (NC) clusters. Fig. 3I STEM-EDS analysis in the Figure 2 shows that FCCNCs contain mainly Pt as well as C and O elements. Through a large number of quantitative measurements, it can be observed that the size of PtNCs is in the range of 3 nm to 7 nm, with a significant lattice expansion compared to bulk Pt ( Figure 3J ).

[0084] like Figures 4A-4C As shown in Figure 2, by utilizing geometric phase analysis (GPA), it is possible to map the lattice strain component distribution of Pt NCs without crystallographic defects such as dislocations. Obviously, the lattice strain field within Pt NCs is heterogeneous, consisting of shear and normal components.

[0085] It is noteworthy that the average normal strain is positive or tensile, which is consistent with the average lattice strain obtained by measuring the lattice constant ( Figure 3F and 3J ). Metal-based nanofilms (e.g., gold or high entropy alloys) synthesized by PSBEE can be viewed as metal-based nanocrystals during metal deposition and stripping. Similarly, the Pt nanofilms of the present invention show heterogeneous nanostructures characterized by nanocrystal assembly and permeation.

[0086] refer to Figures 5A-5CTEM analysis of 5 nm Pt nanofilms revealed the presence of amorphous carbon and dispersed Pt nanoparticles. As amorphous carbon gradually transforms into crystalline Pt, significant lattice distortion is expected, especially in the near-interface region. However, quantitative characterization of strain is challenging due to the mixing of signals from both amorphous and crystalline regions. When the nanofilm thickness increases to 10 nm, the nanoparticles penetrate to form a network structure. These strains are similar to those obtained for 19 nm and 28 nm Pt nanofilms. In addition, it is observed that there are obvious vacancies ( Figure 5D-5E ).

[0087] Example 4

[0088] Electronic properties of Pt nanofilms

[0089] like Fig. 6A As shown, in order to further characterize the chemical properties of the Pt nanofilm, X-ray photoelectron spectroscopy (XPS) was performed. The XPS spectra of Pt, C, and O observed after different etching times showed two prominent peaks at 71.1 eV and 74.5 eV, which correspond to Pt in its metallic state. 0 . Although no oxides were found in the current Pt nanofilms, the two peaks slightly extend to higher binding energies, which are close to the binding energy of Pt oxides. The XPS spectrum of C 1s shows four different peaks at approximately 282.9 eV, 284.8 eV, 286.2 eV, and 288.5 eV, which are attributed to C=C, CC, CO, and C=O, respectively. These chemical bonds are expected to be the residues of decomposed PVA during the exfoliation of 2D metals. The XPS spectrum of O 1s exhibits two main peaks at approximately 532.2 eV and 533 eV, corresponding to CO and C=O, respectively, which provides further evidence of decomposed PVA. No signs of Pt oxides were observed. However, Pt 0 The binding energy distribution of Pt nanocrystals exhibits a shift towards higher energy values, an observation that may be attributed to the lattice distortion within the Pt nanocrystals.

[0090] Figure 6B The relative concentrations of Pt, C, and O are shown as a function of etching time, demonstrating the chemical gradient in the Pt nanofilm. The compositional changes with etching time are mainly attributed to the formation of gradient nanostructures due to the reaction of metal and PVA. This phenomenon of gradient nanostructures was also observed in gold nanofilms made using PSBEE.

[0091] In addition, X-ray absorption spectroscopy (XAS) was performed on the Pt nanofilm and two reference materials (e.g., Pt flakes and PtO2) ( Figure 6C). Due to the presence of metallic Pt, the Pt L3 edge threshold energy and maximum energy for X-ray absorption of Pt nanofilms appear to be very similar to those of Pt foils. However, the maximum absorption energy of Pt nanofilms is slightly higher than that of Pt foils (Pt 0 ), but significantly less than the maximum absorption energy of PtO2 (Pt IV ). This behavior indicates that although metallic Pt bonding is dominant, there is still a tendency for a cationic environment to form around Pt. The Fourier transform of the extended X-ray absorption fine structure (EXAFS) region yields two prominent peaks at approximately 2.7 Å and 1.7 Å, corresponding to Pt-Pt and Pt-C / O coordination, respectively ( Fig.6D ). refer to Figure 6E-6F As shown in Table 1, EXAFS analysis shows that the average Pt coordination number of the Pt nanofilm is about 9.7, which is smaller than the conventional Pt coordination number (=12), indicating the presence of defective atomic structure in the Pt nanofilm. Figure 6G The curves of EXAFSχ(k) signals of Pt nanofilm, PtO2 and Pt foil with respect to k space are shown. According to the curves, it can be seen that the Pt nanofilm is similar to the Pt foil. In addition to the Pt-Pt bonds, a small amount of Pt-C / O bonds ( Figure 6H ). It is noteworthy that similar results were also observed for 28 nm thick Pt nanofilms.

[0092] Table 1 EXAFS fitting parameters (S0) of Pt foil and Pt nanofilm at Pt L3 edge 2 =0.839) a CN: coordination number; b R: distance to adjacent atoms; c σ 2 : mean square relative displacement (MSRD); d ΔE0: internal potential correction; R factor indicates goodness of fit. By fixing CN to the known crystallographic value, S0 is fitted according to the experimental EXAFS of Pt foil. 2 Fixed at 0.839.

[0093] Due to the limitation of EXAFS technique, Pt-C and Pt-O cannot be directly distinguished, and measuring their coordination numbers has proven to be challenging. Figure 6B Based on the observation in , the coordination number of Pt-C is larger than that of Pt-O, which is reasonable. Based on this reasoning, it is expected that the coordination number of Pt-C / O will increase with decreasing thickness. This is supported by the EXAFS data of 19 nm and 28 nm Pt nanofilms (Table 1). However, there is no clear trend indicating that the Pt-C / O ratio significantly affects the HER performance.

[0094] Example 5

[0095] Configuration of water splitting device

[0096] To fabricate the water splitting device, a serpentine flow field using S-shaped titanium was used as a bipolar plate to separate the two electrodes and collect the current. The PEM-WE electrolyzer was assembled in the following order: end plate, sealing gasket, titanium current collector, 19 nm Pt nanomembrane on carbon cloth, proton exchange membrane, IrO2, titanium current collector, sealing gasket, and end plate ( Figure 1 The anode consisted of IrO2 (99.9%, Macklin) with a mass loading of 0.43 mg cm -2 The total geometric area of ​​the cathode and anode is 4.0 cm 2 A proton exchange membrane (DuPont Nafion PFSA N117) was used to separate the cathode and anode compartments of the electrolyzer. For the test, a peristaltic pump was used to control the flow of 2.5 ml min -1 0.5 M H2SO4 electrolyte was supplied to both sides of the electrolyzer at a rate of 1.3 Å. The cell voltage measured in a PEM electrolyzer without IR compensation is reported.

[0097] Example 6

[0098] Electrochemical characterization in acidic electrolytes

[0099] To evaluate its electrocatalytic properties, the Pt nanofilm was transferred onto commercial carbon cloth to test the HER. Figures 7A-7C As shown, the nanomembrane of the present invention is wrapped around the individual carbon fibers in the carbon cloth after the nanomembrane is transferred due to Van der Waals force.

[0100] Electrochemical measurements were performed on an electrochemical workstation (Iviumstat Technology) using a conventional three-electrode cell in 0.5 M H2SO4 at room temperature. Graphite rods and saturated calomel were used as counter and reference electrodes, respectively. Figure 7D-7E shown. Fig.7D The results show that the Pt nanofilm used as an electrocatalyst exhibits a significantly lower onset potential than bulk Pt foil, indicating its superior performance. The η10 (i.e., the peak current at 10 mA / cm2) of the four Pt nanofilms with different thicknesses was extracted from the polarization curves. 2 The overpotential under the condition of Fig. 7E). It is noteworthy that the η10 of the Pt nanofilm catalyst is in the range of 26mV to 29mV, which is much smaller than the η10 of the Pt foil catalyst (=46mV). The Tafel slope of the Pt nanofilm catalyst is in the range of 30mV / dec to 37mV / dec, indicating a mechanism that combines the Volmer-Tafel reaction and the Volmer-Heyrovsky reaction. Similarly, the electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) results also show that the HER performance of the nanofilm is better than that of the Pt foil ( Figures 8A-8B ).

[0101] In addition, the catalyst loading of Pt nanofilms was measured by inductively coupled plasma optical emission spectroscopy (ICP-OES), since mass activity and turnover frequency (TOF) are another important indicators for evaluating the potential scalability of metal-based electrocatalysts. Figure 2 ), and calculate its mass activity at an overpotential of 50 mV. Fig. 9 As shown, the mass activity of the Pt nanofilm increases from 1.4 for the 19 nm thick nanofilm to 4.4 for the 5 nm thick nanofilm, which is about five orders of magnitude higher than the mass activity of bulk Pt foil (5.7×10-5) and one order of magnitude higher than the mass activity of commercial Pt / C (0.3).

[0102] The catalytic efficiency of each Pt site was further quantified using TOF. As shown in Table 2, the TOF values ​​of the Pt nanofilm at an overpotential of 100 mV ranged from 48.3 to 145.7 S -1 The TOF value is significantly higher than that of most HER catalysts. Fig. 10A It was also determined that the Pt nanofilms of different thicknesses at 10 mA / cm 2 It is noteworthy that these curves exhibit a high degree of overlap, indicating excellent stability.

[0103] In addition, the performance of Pt nanofilms was compared with other reported electrocatalysts in terms of η10 and Tafel slope. Fig. 10B As shown, the Pt nanofilm of the present invention exhibits very excellent performance.

[0104] Table 2 - Summary of TOF values ​​and current density of Pt nanofilms of the present invention and other Pt-based catalysts in 0.5M H2SO4 at an overpotential of 100 mV

[0105] In addition, the morphology of the Pt nanofilm and the Pt concentration in the electrolyte were examined after the stability test. Fig.11 As shown, after long-term testing, the Pt nanofilm still adhered to the carbon fiber and the Pt ion concentration in the solution was negligible (2.2 μg / L).

[0106] At 10mA / cm 2 After a 24-hour stability test at a current density of 1.5 Å, an extensive XPS analysis was performed. The results showed that regardless of the etching time, there were two prominent peaks at 71.1 eV and 74.5 eV, corresponding to the metallic state of Pt (Pt 0 ). In addition, O 1s analysis showed no signs of metal oxides or any peaks in the range of 529-530 eV, further demonstrating the excellent electrochemical stability of the Pt nanofilm.

[0107] It was observed that in Pt 0 There is a significant skew in the binding energy distribution towards high energy values, indicating that the Pt nanocrystals may be further distorted after the stability test. The SEM results show that most of the Pt nanofilm is still adhered to the carbon fiber, with some micro-scale cracks. It should be noted that with decreasing thickness, the Pt nanofilm (5 nm) tends to break in a brittle mode, making it difficult to transfer without extensive premature failure. As a demonstration of future industrial applications, 19 nm Pt nanofilms were selected as cathode HER catalysts due to their ease of transfer, and commercial IrO2 was selected as the anode OER catalyst in the PEM-WE device ( Fig.12 ). At 10mA / cm 2 At a current density of 2.5 Å, the voltage remains approximately 1.72 V without IR compensation, and the overpotential amplification is negligible even after 100 h of testing.

[0108] Example 7

[0109] mechanism

[0110] It has been demonstrated that elastic strain can enhance electrochemical catalytic reactions by changing the binding energy of intermediates by altering the electronic states at the Fermi level. However, current research has focused on the role of uniform strain applied to ideal crystals. In contrast, Pt nanofilms consist of highly distorted nanocrystals with heterogeneous elastic strain.

[0111] Through atomic force microscopy (AFM) indentation, it was found that the elastic modulus of the Pt nanofilm was as low as 16±2 GPa, which is about 9% of the elastic modulus of 5-nanometer Pt nanocrystals (179 GPa). Figures 13A to 13D). A similar phenomenon of lattice distortion causing modulus reduction has also been observed in high entropy alloys. 6 .

[0112] To understand the origin of such heterogeneous strain, large-scale molecular dynamics (MD) simulations were performed on Pt nanocrystals containing a significant amount of substitutional C atoms. Fig.14A The atomic structure of Pt nanocrystals with substituted C atoms is shown. Fig. 14B The distribution of shear strain and volume strain of Pt nanocrystals with / without surface atoms is shown. The results show that heterogeneous distribution of both shear strain and normal strain is observed on the surface of the nanocrystals. These strains are induced by excessive crystalline defects (especially vacancies) on the surface and within the nanocrystal boundaries (Table 1). Therefore, the observed surface strain distribution is consistent with Figure 4B-4C The experimental results shown in are similar.

[0113] Extensive density functional theory (DFT) simulations were performed to investigate the heterogeneous strain on the surface adsorption behavior of distorted or defective nanocrystals.

[0114] The role of heterogeneous strain was systematically studied. The reference model "ideal Pt nanocrystal" was subjected to uniform strains ranging from 0% to 7% along the (111), (100) and (110) directions. Another atomic model was established to simulate heterogeneous strain with lattice distortion by inserting vacancies on the surface of Pt nanocrystals. Defective Pt nanocrystals were also subjected to tensile strains ranging from 0% to 7% along the (111), (100) and (110) directions. Fig.15 As shown, the simulations reveal that the heterogeneous strain in the distorted nanocrystals leads to an upward shift of the d-band center, facilitating H adsorption regardless of the crystal orientation.

[0115] Then, the Gibbs free energy of hydrogen adsorption on different surfaces was calculated. H *Changes. Figures 16A-16B As shown, the AG of all conventional Pt nanocrystals H * all remain negative and increase with uniform strain. In sharp contrast, when the Pt nanocrystals are severely distorted, AG H * becomes positive. As the distorted Pt nanocrystals are strained, AG H * gradually decreases, and even reaches zero energy at 5% strain on the distorted (111) surface, which is ideal for hydrogen evolution but unattainable by simply straining conventional Pt within the Lindeman strain limit (about 10%), above which the crystal becomes unstable. These important findings suggest that lattice distortion behaves as heterogeneous elastic strain ( Fig. 16B(inset), the hydrogen adsorption energy on the Pt surface can be tuned over a much larger range than conventional elastic strain engineering. This leads to greater tunability of the HER performance. These computational results demonstrate that distorted Pt nanocrystals are more efficient than conventional Pt nanocrystals in catalyzing water splitting. Fig. 16C Free energy calculations of distorted crystals with different vacancies are shown.

[0116] In the present invention, heteroatom doping, such as carbon doping or oxygen doping, is also considered. Initially, an atomic model representing an ideal or non-distorted Pt nanocrystal is constructed as a reference. However, the results show that carbon or oxygen doping has no beneficial effect on the HER performance ( Fig.16D ).

[0117] Cost per unit area of ​​Pt nanofilm

[0118] like Fig.17 As shown, it is clear that the Pt nanofilm (approximately 10 -3 Up to 10 -4 $ / cm 2 ) than Pt foil (about 10$ / cm 2 ) are several orders of magnitude cheaper.

[0119] In summary, the present invention provides ultra-efficient and affordable Pt nanofilm electrocatalysts for HER, which exhibit excellent electrochemical stability through PSBEE. Enhanced HER performance is achieved by inducing lattice distortion and heterogeneous strain in Pt nanofilms. In addition, due to the ultrathin nature of Pt nanofilms, they are highly cost-effective and even comparable to non-precious metal catalysts. Since PSBEE can be used to fabricate various metal and ceramic nanofilms regardless of their chemical composition, this approach is promising for the development of low-dimensional electrocatalysts for many other key electrochemical reactions.

[0120] The above description of the present invention has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. For those skilled in the art, many modifications and variations will be apparent.

[0121] The embodiment was chosen and described in order to best explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the invention for various embodiments and with various modifications as are suited to the particular use contemplated.

[0122] Industrial Applicability:

[0123] The present invention proves that the PSBEE method is a simple, scalable process that can produce a large number of metal-based nanofilms (such as Au, high entropy alloys and Pt) at low cost. This makes it promising for the synthesis of next-generation low-dimensional electrocatalysts. Most importantly, unlike other 2D and conventional electrocatalysts, the Pt nanofilms synthesized by PSBEE in the present invention have a unique nanostructure consisting of severely distorted nanocrystals. A large number of atomic-scale defects (i.e., vacancies) caused by lattice distortion and the resulting heterogeneous strain work together to enhance the HER catalytic performance of the Pt nanofilm. This enables them to surpass commercial Pt electrocatalysts and many other conventional Pt electrocatalysts.

[0124] Pt nanofilms have excellent electrical conductivity, catalytic activity, biocompatibility, optical properties and mechanical properties. These properties provide a wide range of application prospects in fields such as energy, catalysis, biomedicine and nanotechnology. Application examples include but are not limited to: oxygen reduction reaction (ORR) in fuel cells, HER in water electrolysis, oxygen reduction reaction (ORR) in metal-air batteries, etc.

[0125] definition

[0126] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations thereof (such as "comprises" or "comprising") should be understood to imply the inclusion of the stated integer or groups of integers, but not the exclusion of any other integer or groups of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising", etc. may have the meaning ascribed to them in U.S. patent law, such as to allow for elements not expressly recited, but to exclude elements found in the prior art or elements that affect the basic or novel characteristics of the invention.

[0127] In addition, throughout the specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.

[0128] As used herein and not otherwise defined, the terms "substantially," "essentially," "approximately," and "about" are used to describe and explain small variations. When used in conjunction with an event or circumstance, the terms may encompass instances where the event or circumstance occurs exactly as well as instances where the event or circumstance occurs close to occurring. For example, when used in conjunction with a numerical value, the terms may encompass a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.

[0129] References in this specification to "one embodiment", "an embodiment", "example embodiment", etc. indicate that the described embodiment may include certain features, structures, or characteristics, but not every embodiment must include certain features, structures, or characteristics. In addition, such phrases do not necessarily refer to the same embodiment. Further, when a certain feature, structure, or characteristic is described in conjunction with an embodiment, it is considered to be within the knowledge of those skilled in the art to affect such feature, structure, or characteristic in conjunction with other embodiments, whether or not explicitly described.

[0130] In the preparation method described herein, except for the case of explicitly stating the time or operation sequence, the steps can be performed in any order without departing from the principles of the present invention. The description in a certain claim to the effect that a certain step is performed first, and then several other steps are subsequently performed should be considered to mean that the execution of the first step precedes any step in the other steps, but the other steps can be performed in any appropriate order unless the order is further described in the other steps. For example, the claim element of "step A, step B, step C, step D and step E" should be interpreted as meaning that step A is performed first and step E is performed last, and step B, step C and step D can be performed in any order between step A and step E, and the order still falls within the literal scope of the process claimed for protection. A given step or a subset of steps can also be repeated. In addition, unless the clear claim language states that the specified steps are performed separately, the specified steps can be performed simultaneously.

[0131] "Atomic percentage" refers to the percentage of the number of atoms of each element in the composition to the total number of atoms. The atomic percentage of each element in the composition should add up to 100%.

[0132] “η10” represents the potential when the current density reaches 10 mA / cm2, and is usually used to describe the efficiency of electrocatalysts in catalyzing the hydrogen evolution reaction.

[0133] Other definitions of selected terms used herein can be found in the detailed description of the entire invention and application. Unless otherwise defined, all other technical terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs.

[0134] References: The disclosures of the following references are incorporated herein by reference 1. J.N. Tiwari, S.Sultan, C.W. Myung, T.Yoon, N.Li, et al. Multicomponent electrocatalyst with ultralow Pt loading and high hydrogen evolution activity. Nat. Energy 3, 773-782 (2018). 2. D. Liu, X. Li, S. Chen, H. Yan, C. Wang, et al. Atomically dispersed platinum supported on curved carbon supports for efficient electrocatalytic hydrogen evolution. Nature Energy 4, 512-518 (2019). 3. T. Wang, M. Park, Q. He, Z. Ding, Q. Yu, et al., Low-Cost Scalable Production of Freestanding Two-Dimensional Metallic Nanosheets bt Poltmer Surface Buckling Enabled Exfoliation. Cell Reports Phys. Sci. 1, 100235 (2020). 4. T. Wang, Z. Zhang, M. Park, Q. Yu and Y. Yang, Etching-Free Ultrafast Fabrication of Self-Rolled Metallic Nanosheets with Controllable Twisting. Nano Lett. 21, 7159-7165 (2021). 5. T. Wang, Q. He, J. Zhang, Z. Ding, F. Li, et al., The controlled large-area synthesis of two dimensional metals. Mater. Today, 36, 30-39 (2020). 6. QF He, JG Weng, HAChen, ZY Ding, ZQ Zhou, et al., A highly distorted ultraelastic chemically complex Elinvar alloy. Nature 602, 251-257 (2022).

Claims

1. A self-supporting metal-based nanofilm electrocatalyst for sustainable hydrogen production, characterized in that: The self-supporting metal-based nanofilm electrocatalyst includes one or more metal nanocrystals with lattice expansion, wherein the one or more metal nanocrystals include highly distorted heterogeneous nanostructures, the one or more metal nanocrystals are bonded together by nanoscale amorphous carbon interfaces, and lattice distortion and heterogeneous strain are induced in the self-supporting metal-based nanofilm electrocatalyst to enhance hydrogen evolution reaction performance.

2. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the self-supporting metal-based nanofilm exhibits a heterogeneous distribution of local conductivity, and the self-supporting metal-based nanofilm is characterized in that high conductivity nanodomains are surrounded by regions with lower conductivity.

3. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the highly distorted heterogeneous nanostructure comprises FCC nanocrystals and amorphous regions located between the FCC nanocrystal clusters.

4. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the metal is selected from gold, platinum, silver, titanium, palladium, ruthenium, iridium or other high entropy alloys, or a combination thereof. 5 . The self-supporting metal-based nanofilm electrocatalyst according to claim 1 , wherein the self-supporting metal-based nanofilm electrocatalyst comprises 20-80 at % of platinum, 10-50 at % of carbon, and 1-30 at % of oxygen. 6 . The self-supporting metal-based nanofilm electrocatalyst according to claim 1 , wherein the thickness of the self-supporting metal-based nanofilm electrocatalyst is in the range of 1 nm to 30 nm.

7. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the average size of the one or more metal nanocrystals is between 1 nanometer and 10 nanometers.

8. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the self-supporting metal-based nanofilm electrocatalyst does not contain a binder.

9. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the self-supporting metal-based nanofilm electrocatalyst is synthesized by polymer surface buckling exfoliation.

10. The self-supporting metal-based nanofilm electrocatalyst according to claim 9, wherein the polymer surface buckling peeling comprises the following steps: Using a polymer layer on a substrate as a scaffold for supporting a metal film; inducing controlled buckling on the polymer surface; and peeling off the metal film to obtain the self-supporting metal-based nanofilm electrocatalyst.

11. The self-supporting metal-based nanofilm electrocatalyst according to claim 10, wherein the substrate comprises a glass plate or a silicon wafer.

12. The self-supporting metal-based nanofilm electrocatalyst according to claim 10, wherein the polymer comprises polyvinyl alcohol.

13. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the self-supporting metal-based nanofilm electrocatalyst exhibits an η10 value of less than 30 mV.

14. The self-supporting metal-based nanofilm electrocatalyst according to claim 1, wherein the self-supporting metal-based nanofilm electrocatalyst exhibits a Tafel slope in the range of 30 mV / dec to 37 mV / dec.

15. A water splitting device comprising the self-supporting metal-based nanofilm electrocatalyst according to claim 1.

16. A proton exchange membrane fuel cell comprising the self-supporting metal-based nanomembrane electrocatalyst according to claim 1.